Penyuluhan Pengasuhan Efektif di Masa Bencana Melalui Parenting Education Berbasis Online - Wiwiek Zainar Sri Utami; Eneng Garnika; Lu’luin Najwa; Dewi Rayani; Lalu Ari Irawan (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2020)
The purpose of this service activity is to provide the knowledge in education program handling for parents (parenting education) and teachers to increase their treasure of knowledge about children's growth and development and to align children's education at school and home during the Covid-19 pandemic. The method of this community service program was conducted through the online platform